Macroprudential regulation and leakage to the shadow banking sector - Stefan Gebauer; Falk Mazelis (European Central Bank (ECB), 2020)
Macroprudential policies are often aimed at the commercial banking sector, while a host of other non-bank financial institutions, or shadow banks, may not fall under their jurisdiction. We study the effects of tightening commercial bank regulation on the shadow banking sector. We develop a DSGE model that differentiates between regulated, monopolistic competitive commercial banks and a shadow banking system that relies on funding in a perfectly competitive market for investments. After estimating the model using euro area data from 1999-2014 including information on shadow banks, we find that tighter capital requirements on commercial banks increase shadow bank lending, which may have adverse financial stability effects. Coordinating macroprudential tightening with monetary easing can limit this leakage mechanism, while still bringing about the desired reduction in aggregate lending. In a counterfactual analysis, we compare how macroprudential policy implemented before the crisis would have dampened the business and lending cycles.
Keywords: E32; E58; G23; 330; Macroprudential Policy; Monetary Policy; Policy Coordination; Non-BankFinancial Institutions; Financial Frictions